Studies on electron linear accelerator system for polymer reseach - E. Kongmon (2018)
Copyright © 2016 CC-BY-3.0 and by the respective authors. This research focuses on modification of an electron linear accelerator system for irradiation of natural rubber latex and polymeric materials at the Plasma and Beam Physics Research Facility, Chiang Mai University, Thailand. This is in order to study the change of material properties due to electron beam irradiation. The main accelerator system consists of a DC thermionic electron gun and a short standing-wave linac. This system will be able to produce electron beams with variable energy in the range of 0.5 to 4 MeV. The linac macro pulse frequency is adjustable within the range of 20 to 1000 Hz. The macro pulse duration is 4 μs. The electron pulse current can be varied from 10 to 100 mA. This lead to the electron dose of about 0.44 to 4.4 Gy-m2/min. In this paper, overview of the accelerator and the irradiation system is presented. Results of low-level RF measurements of the accelerating structure are also reported and discussed.